2022
DOI: 10.1007/s40618-022-01872-w
|View full text |Cite
|
Sign up to set email alerts
|

Health-related quality of life in patients with neuroendocrine neoplasms: a two-wave longitudinal study

Abstract: Purpose Scientific knowledge on health-related quality of life (HRQoL) in patients with neuroendocrine neoplasm (NEN) is still limited and longitudinal assessment of HRQoL over the time in NEN patients are scarce. The current study aimed to assess the role of clinical severity and heterogeneity of NEN, as well as resilience, in the HRQoL of NEN patients over the course of a year. Methods 39 consecutive NEN patients (25 men and 14 women) aged from 29 to 73 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 29 publications
0
10
0
Order By: Relevance
“…Depression is a common complication that occurred in about 20-25% of cancer survivors [19,20]. Growing studies accumulated to explore the associations of mental health with mortality among patients with lung cancer [21], prostate cancer [22], esophageal cancer [23], neuroendocrine neoplasms [24,25], and breast cancer [26][27][28], yet the findings are still inconsistent, more evidences are warranted regarding to this setting. Moreover, at the behavioral level, mental health and healthy lifestyle can influence and reinforce each other.…”
mentioning
confidence: 99%
“…Depression is a common complication that occurred in about 20-25% of cancer survivors [19,20]. Growing studies accumulated to explore the associations of mental health with mortality among patients with lung cancer [21], prostate cancer [22], esophageal cancer [23], neuroendocrine neoplasms [24,25], and breast cancer [26][27][28], yet the findings are still inconsistent, more evidences are warranted regarding to this setting. Moreover, at the behavioral level, mental health and healthy lifestyle can influence and reinforce each other.…”
mentioning
confidence: 99%
“…35 It was also found that, in rare cancers, the clinical severity of the tumor, such as the presence or absence of metastases or comorbidities, and the tumor heterogeneity, such as the primary site, had obvious impact on physical symptoms and financial problems. 36,39 These studies highlighted that cancer patients may experience a range of competing comorbidities that are significant to HRQoL and, in some cases, have a greater impact on physical health than mental health. This study contributes to the evidence on multimorbidity and financial well-being as predictors of HRQoL in cancer patients by conducting a mediation analysis in which the total effect is divided into direct and indirect effects.…”
Section: Discussionmentioning
confidence: 99%
“…The multicollinearity of the independent variables in the linear regressions was assessed using their variance inflation factors (VIFs). The significance of the mediating effect on a HRQoL outcome was assessed based on the bias‐corrected bootstrapped 95% confidence interval of the indirect effect of multimorbidity on the underlying outcome through financial well‐being, with 10,000 replications 36 . Further analyses with adjustments for covariates, such as age, sex, marital status, educational attainment, household monthly income, employment status, living arrangements, and insurance status, were conducted to examine the robustness of the mediation analysis results.…”
Section: Methodsmentioning
confidence: 99%
“…Resilience mediates the relationship between the use of coping strategies and quality of life ( 16 ). Two recent multicentric studies evaluated resilience as a protective factor against the negative effects of NET on health-related quality of life ( 37 , 38 ). Hence, we consider coping and resilience as critical elements able to alleviate distress and promote quality of life in patients with GEP-NETs, and psycho-oncologists should provide coping-strategy training and evidence-based resilience interventions for the patients.…”
Section: Discussionmentioning
confidence: 99%